2012
DOI: 10.1111/jbg.12009
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of genetic diversity in Bolivian llama populations using microsatellites

Abstract: South American camelids (SACs) have a major role in the maintenance and potential future of rural Andean human populations. More than 60% of the 3.7 million llamas living worldwide are found in Bolivia. Due to the lack of studies focusing on genetic diversity in Bolivian llamas, this analysis investigates both the genetic diversity and structure of 12 regional groups of llamas that span the greater part of the range of distribution for this species in Bolivia. The analysis of 42 microsatellite markers in the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
7
0
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 26 publications
3
7
0
2
Order By: Relevance
“…Thus, our results might indicate that this management strategy has contributed to maintaining high genetic variability, and it will be complemented with the routine assessment of the genetic variability by means of molecular markers such as microsatellites or single-nucleotide polymorphisms (SNPs). Furthermore, our results are similar to those from Argentinean (7.33-8.33 mean alleles per microsatellite and He of 0.47-0.9; [1,52]) and Bolivian (12.04 alleles per microsatellite and He = 0.68) llama populations [2]. Likewise, in those studies, the He was always higher than the Ho, and a higher value of He was reported in the Quimsachata llama population compared to the Bolivian llama population.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…Thus, our results might indicate that this management strategy has contributed to maintaining high genetic variability, and it will be complemented with the routine assessment of the genetic variability by means of molecular markers such as microsatellites or single-nucleotide polymorphisms (SNPs). Furthermore, our results are similar to those from Argentinean (7.33-8.33 mean alleles per microsatellite and He of 0.47-0.9; [1,52]) and Bolivian (12.04 alleles per microsatellite and He = 0.68) llama populations [2]. Likewise, in those studies, the He was always higher than the Ho, and a higher value of He was reported in the Quimsachata llama population compared to the Bolivian llama population.…”
Section: Discussionsupporting
confidence: 90%
“…Likewise, in those studies, the He was always higher than the Ho, and a higher value of He was reported in the Quimsachata llama population compared to the Bolivian llama population. Nonetheless, it is important to mention that they used different sets of microsatellite markers (many of which were individually used in this study), and in the case of Barreta et al (2013), they were not necessarily specific for SACs. Thus, to make a more adequate comparison, we would ultimately have to use the same set of microsatellites used in those studies.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The United Nations Human Development Index ranks Bolivia 118 th out of 188 countries, with 45% of the population living below the poverty line (UNHDI, 2016). Llama husbandry is recognized as an important element of the Altiplano ecosystem (Barreta et al, 2013;Treydte, Salvatierra, Sauerborn, & Lamers, 2011;Postigo, Young, & Crews, 2008;Fairfield, 2004) as it ensures soil fertility and seed dispersal while providing a livelihood and a source of many goods and services for rural communities. Small ruminant (llama and sheep) husbandry is the principal economic activity for more than 54 000 rural poor families in Bolivia, while 3 000 families pursue llama husbandry as their primary source of income (Barreta et al, 2013;Vera, 2006).…”
Section: Introductionmentioning
confidence: 99%